“HUKUM PERNIKAHAN LAKI-LAKI MUSLIM DENGAN PEREMPUAN NON MUSLIM (Studi Analisis Maqâshid Al-Syarî’ah terhadap Pendapat Muhammad Rasyîd Ridhâ dan Fatwa Majelis Ulama Indonesia)” - Fauzan Alfajri; Firdaus Firdaus (Jurnal AL-AHKAM, 2020)
This research was motivated by differences of opinion between Muhammad Rasyîd Ridha and the Indonesian Ulema Council No. 05 / Kep / Munas II / MUI / 1980 concerning the Law of Muslim Men  Marrying  Non-Muslim  Women.  In  the  opinion  of  Muhammad  Rasyîd  RidhâAhl  al-Kitâb  are those who have a holy book that is believed to have been sent down by God, marrying Ahl al-Kitâb is permissible.  On  this  basis  it  is  permissible  to  marry  a  non-Muslim  woman  Ahl  al-Kitâb.  While marrying  an  idolatrous  woman  is  haram,  the  idolatrous  woman  in  question  was  an  Arabic idolatrous  at  the  time  when  the  Qur'an  was  revealed.  Meanwhile,  according  to  the  Indonesian Ulema  Council,  marrying  a  woman  from  Ahl  al-Kitâb,  there  are  differences  in  the  opinion  of  the scholars,  in  line  with  that  it  is  haram  to  marry  a  non-Muslim  woman.  There  are  two  things  that form  the  problem  of  this  thesis.  First,  what  are  the  factors  that  cause  differences  in  opinion  of Muhammad  Rasyîd  Ridhâ  and  the  Indonesian  Ulema  Council.  Second,  what  is  the  opinion  of Muhammad Rasyîd Ridhâ and the Fatwa of the Indonesian Ulema Council in terms of maqâshid al- syarî'ah ?.   This  research  is  a  research  library  (library  research)  because  the  data  needed  for  the preparation of this scientific work are contained in primary sources in the form of Tafsir al-Manar, a  collection  of  Fatwa  Muhammad  Rasyîd  Ridhâ  and  a  collection  of  Fatwas  from  the  Indonesian Council. In addition, the secondary sources of this study were taken from the literature related  to inter-marriage.  After  the  data  was  collected,  the  writer  classified  and  analyzed  it  by  using  the inductive  method.  The  research  findings  are  first,  the  cause  of  the  difference  in  opinion  between Muhammad  Rasyîd  Ridhâ  and  the  Fatwa  of  the  Indonesian  Ulema  Council  is  different  in understanding the argument. The argument used by Muhammad Rasyîd Ridhâ is the zhahir verse of QS al-Maidah verse 5, while the Indonesian Ulama Council because there is a difference in ulama, the Indonesian Ulama Council chose an opinion that is forbidden because it considers the harm to be  greater  than  the  benefits.  The  argument  used  by  the  Indonesian  Ulema  Council  is  mashlahah dharûriyah.  Second,  the  opinion  of  Muhammad  Rasyîd  Ridhâ  which  allows  marrying  non-Muslim women (Ahl al-Kitâb) by adhering to zahirnash in line with maqâshid al-syarî'ah, in this case there is one method of knowing the meaning shari 'namely bi zhawahiri al-nushush (text). Keywords: Nikah, Maqâshid al-Syarî'ah', Muhammad Rasyîd Ridhâ, Indonesian Ulema Council.